2016
DOI: 10.3390/ijms17030318
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Toxic Pyrrolizidine Alkaloids and Their Common Hepatotoxicity Mechanism

Abstract: Pyrrolizidine Alkaloids (PAs) are currently one of the most important botanical hepatotoxic ingredients. Glutathion (GSH) metabolism is the most reported pathway involved in hepatotoxicity mechanism of PAs. We speculate that, for different PAs, there should be a common mechanism underlying their hepatotoxicity in GSH metabolism. Computational methods were adopted to test our hypothesis in consideration of the limitations of current experimental approaches. Firstly, the potential targets of 22 PAs (from three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Covalent GSH conjugates with dehydropyrrolizidine were identified as metabolites of senecionine and several other PAs, and considered as an indirect confirmation of the bioactivation pathway (Chen et al 2016 ; Geburek et al 2020 ; Huan et al 1998b ; Lin et al 1998 ; Ramsdell and Buhler 1987 ; Reed et al 1992 ). A study by Yan et al investigated 22 PAs as potential targets in GSH metabolism, and they identified glutathione S-transferase A1 (GSTA1) and glutathione peroxidase 1 (GPX1) as protein targets (Yan et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Covalent GSH conjugates with dehydropyrrolizidine were identified as metabolites of senecionine and several other PAs, and considered as an indirect confirmation of the bioactivation pathway (Chen et al 2016 ; Geburek et al 2020 ; Huan et al 1998b ; Lin et al 1998 ; Ramsdell and Buhler 1987 ; Reed et al 1992 ). A study by Yan et al investigated 22 PAs as potential targets in GSH metabolism, and they identified glutathione S-transferase A1 (GSTA1) and glutathione peroxidase 1 (GPX1) as protein targets (Yan et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of PAs-induced hepatotoxicity appear to be related to the binding of the active metabolites and DNA/protein [49,50]. The detailed mechanisms of liver injury induced by PAs have been extensively reviewed elsewhere [51,52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Natural toxins are also found in many medicinal herbs; for example, compounds such as pyrrolizidine alkaloids are naturally occurring in comfrey, among other plants, and are toxic to humans and livestock (Roeder, 1995). Pyrrolizidine alkaloids are known hepatotoxins and have also been associated with neurotoxicity, pneumotoxicity, embryo-fetal toxicity, and carcinogenicity (Fu et al, 2001; Neuman et al, 2015; Seaman, 1987; Yan et al, 2016). There are four plant families that commonly contain high levels of pyrrolizidine alkaloids, including Asteraceae, Boraginacceae, Leguminosae, and Orchidaceae ; however, over 660 unique pyrrolizidine alkaloids and their derivatives have been identified in thousands of different plants (Chou and Fu, 2006; Roeder, 1995; Roeder et al, 2015; Stegelmeier et al, 1999; Yan et al, 2016).…”
Section: The Complexity Of Botanical Dietary Supplementsmentioning
confidence: 99%